Optimalisasi Komunitas Belajar di SD Muhammadiyah Mlangi dalam Pemanfaatan Platform Merdeka Mengajar - Triarini, Dita; Hidayati, Dian; Pangesti, Sriningsih Wahyu (UMSU, 2024)
The vision of the Merdeka Mengajar Platform is to create a collaborative learning environment by developing learning efficiencies and positive working environments. The purpose of this study is to find answers on how the learning community at Muhammadiyah Mlangi Elementary School can be optimized using the Merdeka educational platform. The research was conducted using a qualitative approach with observation, interviews with school principals and teachers participating in learning communities, as well as literature studies. The study concludes that using her PMM with the support of school leaders to optimize learning communities can help school members drive change. In addition, good cooperation between teachers is required for optimal PMM training. This improves self-efficacy and has a positive effect on good learning practices in the classroom.